Hormonal Orchestration of Bud Dormancy Cycle in Deciduous Woody Perennials - Liu, Jianyang; Sherif, Sherif M. (Frontiers in Plant Science, 2019)
Woody perennials enter seasonal dormancy to avoid unfavorable environmental conditions. Plant hormones are the critical mediators regulating this complex process, which is subject to the influence of many internal and external factors. Over the last two decades, our knowledge of hormone-mediated dormancy has increased considerably, primarily due to advancements in molecular biology, omics, and bioinformatics. These advancements have enabled the elucidation of several aspects of hormonal regulation associated with bud dormancy in various deciduous tree species. Plant hormones interact with each other extensively in a context-dependent manner. The dormancy associated MADS (DAM) transcription factors appear to enable hormones and other internal signals associated with the transition between different phases of bud dormancy. These proteins likely hold great potential in deciphering the underlying mechanisms of dormancy initiation, maintenance, and release. In this review, a recent understanding of the roles of plant hormones, their cross talks and their potential interactions with DAM proteins during dormancy is discussed.